Epidemiological surveillance of herpesviral encephalitis in Cordoba, Colombia (2016)
Objetive To establish an epidemiological surveillance of viral herpes encephalitis in major hospitals of Monteria, Cordoba. Methods From September 2009 to December 2011, a descriptive study of cases of viral encephalitis was made in three hospitals in the city of Monteria. Cerebrospinal fluid (CSF) samples from 118 patients were included in the study. Clinical aspects, as well as cytochemical and microbiological analysis (Gram stain and culture) of CSF, were used for selecting the patients. Virus detection was performed by using multiplex nested PCR for Herpes simplex virus 1 and 2, Epstein Barr virus, Cytomegalovirus and Varicella zoster virus.Results Viral DNA of herpesvirus was detected in the CSFs of 30 (25.4 %) participants, as follows: 22 (18.6 %) Herpes simplex 1 and 2 viruses, 4 (3.3 %) Cytomegalovirus and 1 (0.8 %) Varicella zoster virus. Co-infections were observed in 3 patients (2.5 %), 1 case by HSV-VZV and 2 cases by CMV/HSV. The clinical manifestations of the patients included: headache (18.6 %), fever (14.4 %), asthenia (10.1 %), seizures (9.3 %), vomiting (8.4 %), and stiff neck (5.9 %). Thirty percent of the patients also had HIV-AIDS. A case fatality rate of 20 % was observed for the patients.Conclusions This paper shows that herpesvirus is a cause of infection of the CNS in patients from Cordoba. This study contributes to the epidemiology of encephalitis, as well as to patient management.